Kinerja Keuangan: Pendekatan Time Series - Kamila, Dhea Zalsa; Abdullah, Andi Ruslan; Suwandi, Suwandi; Syamsuriani, Syamsuriani (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This study aims to determine and analyze the financial performance of Mandiri Perkasa Interior based on the time series approach. The type of data used in this study is quantitative data sourced from financial statements, namely the balance sheet and income statement of Mandiri Perkasa Interior. The results showed that there was an increase in almost all items or accounts contained in the balance sheet and income statement. So it can be assumed that the financial performance of Mandiri Perkasa Interior based on the time series approach is quite good because it has increased from year to year.